PENGARUH INDEPENDENSI, PENGALAMAN KERJA AUDITOR, DAN INTEGRITAS TERHADAP KUALITAS AUDIT DENGAN SKEPTISISME PROFESIONAL SEBAGAI VARIABEL MODERASI - Khasanah, Magnalia Restu; Haryono, Haryono; Kurniawan, Rudy (Papanda Publisher, 2025)
This study aims to test and analyze the effect of independence, auditor work experience, and integrity with professional scepticism as the moderating variable on audit quality. The sample used in this study was 42 respondents with primary data taken using a questionnaire on auditors working at the Financial and Development Supervisory Board Representative Office of West Kalimantan using the WarpPLS software application version 8.0 with the Structural Equation Modeling (SEM) method. The results of the study indicate that: (1) Independence has no significant effect on audit quality. (2) Auditor work experience has a positive and significant effect on audit quality. (3) Integrity has a positive and significant effect on audit quality. (4) Professional scepticism moderates the effect of independence on audit quality significantly but negatively. (5) Professional scepticism moderates the effect of work experience on audit quality positively and significantly. (6) Professional scepticism moderates the effect of integrity on audit quality significantly but negatively. Keywords: Independence, Auditor Work Experience, Integrity, Professional Scepticism, Audit Quality